Enhancing fatty acid utilization ameliorates mitochondrial fragmentation and cardiac dysfunction via rebalancing optic atrophy 1 processing in the failing heart - Guo, Yongzheng; Wang, Zhen; Qin, Xinghua; Xu, Jie; Hou, Zuoxu; Yang, Hongyan; Mao, Xuechao; Xing, Wenjuan; Li, Xiaoliang; Zhang, Xing; Gao, Feng (Cardiovascular research, 2018)
Heart failure (HF) is characterized by reduced fatty acid (FA) utilization associated with mitochondrial dysfunction. Recent evidence has shown that enhancing FA utilization may provide cardioprotection against HF. Our aim was to investigate the effects and the underlying mechanisms of cardiac FA utilization on cardiac function in response to pressure overload. Transverse aortic constriction (TAC) was used in C57 mice to establish pressure overload-induced HF. TAC mice fed on a high fat diet (HFD) exhibited increased cardiac FA utilization and improved cardiac function and survival compared with those on control diet. Such cardioprotection could also be provided by cardiac-specific overexpression of CD36. Notably, both HFD and CD36 overexpression attenuated mitochondrial fragmentation and improved mitochondrial function in the failing heart. Pressure overload decreased ATP-dependent metalloprotease (YME1L) expression and induced the proteolytic cleavage of the dynamin-like guanosine triphosphatase OPA1 as a result of suppressed FA utilization. Enhancing FA utilization upregulated YME1L expression and subsequently rebalanced OPA1 processing, resulting in restoration of mitochondrial morphology in the failing heart. In addition, cardiac-specific overexpression of YME1L exerted similar cardioprotective effects against HF to those provided by HFD or CD36 overexpression. These findings demonstrate that enhancing FA utilization ameliorates mitochondrial fragmentation and cardiac dysfunction via rebalancing OPA1 processing in pressure overload-induced HF, suggesting a unique metabolic intervention approach to improving cardiac functions in HF.